2005
DOI: 10.1111/j.1365-2710.2005.00651.x
|View full text |Cite
|
Sign up to set email alerts
|

Ketoconazole increases plasma concentrations of antimalarial mefloquine in healthy human volunteers

Abstract: Co-administration with ketoconazole increased plasma mefloquine concentrations in healthy human volunteers. One of possible mechanisms of the increase in plasma mefloquine concentrations may be the result of the inhibition of CYP3A4 by ketoconazole. In case of mefloquine is co-administered with ketoconazole, drug-drug interactions should be recognized and the dose of mefloquine should be adjusted to maximize the therapeutic efficacy and to reduce the cost of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 19 publications
(27 reference statements)
0
23
0
Order By: Relevance
“…A number of studies have demonstrated that coadministration of metabolic inhibitors can enhance the pharmacokinetic profile of antiparasitic drugs and so − no noticeable disruption, + general/mild disruption, ++ severe disruption, +++ very severe disruption, KTZ ketoconazole, NADPH nicotinamide adenine dinucleotide phosphate, TCBZ triclabendazole, TCBZ.SO triclabendazole sulphoxide increase their bioavailability: studies not just on benzimidazoles (Luder et al 1986;Bekhti and Pirotte 1987;Wen et al 1996;Prichard 1991, 1992a, b;Lanusse et al 1992;López-García et al 1998;McKellar et al 2002;Sánchez et al 2002;Merino et al 2003a, b), but on other compounds such as macrocyclic lactones (Hugnet et al 2007;Alvinerie et al 2008), the anti-schistosomal drug, praziquantel (Diekmann et al 1989;Ridtitid et al 2007) and the anti-malarial, mefloquine (Ridtitid et al 2005;Wisedpanichkij et al 2009). The potentiation of drug availability observed has lead a number of workers to propose the use of such drug combinations as a strategy to deal with drug resistance (Lanusse and Prichard 1993;Lanusse et al 1995;Benchaoui and McKellar 1996;Dupuy et al 2003;Sánchez-Bruni et al 2005;Alvinerie et al 2008;Wisedpanichkij et al 2009).…”
Section: Discussionmentioning
confidence: 98%
“…A number of studies have demonstrated that coadministration of metabolic inhibitors can enhance the pharmacokinetic profile of antiparasitic drugs and so − no noticeable disruption, + general/mild disruption, ++ severe disruption, +++ very severe disruption, KTZ ketoconazole, NADPH nicotinamide adenine dinucleotide phosphate, TCBZ triclabendazole, TCBZ.SO triclabendazole sulphoxide increase their bioavailability: studies not just on benzimidazoles (Luder et al 1986;Bekhti and Pirotte 1987;Wen et al 1996;Prichard 1991, 1992a, b;Lanusse et al 1992;López-García et al 1998;McKellar et al 2002;Sánchez et al 2002;Merino et al 2003a, b), but on other compounds such as macrocyclic lactones (Hugnet et al 2007;Alvinerie et al 2008), the anti-schistosomal drug, praziquantel (Diekmann et al 1989;Ridtitid et al 2007) and the anti-malarial, mefloquine (Ridtitid et al 2005;Wisedpanichkij et al 2009). The potentiation of drug availability observed has lead a number of workers to propose the use of such drug combinations as a strategy to deal with drug resistance (Lanusse and Prichard 1993;Lanusse et al 1995;Benchaoui and McKellar 1996;Dupuy et al 2003;Sánchez-Bruni et al 2005;Alvinerie et al 2008;Wisedpanichkij et al 2009).…”
Section: Discussionmentioning
confidence: 98%
“…17,23,24 Also, a few studies have shown that the metabolism of quinine through the CYP 3A4 pathway was inhibited in vivo by CYP 3A4 inhibitors such as ritonavir and ketoconazole. [25][26][27] Therefore, there is a possibility of drug-drug interactions, especially at metabolic pathways if quinine and ciprofloxacin are concurrently administered. However, there is sparse information regarding such interaction between quinine and ciprofloxacin, and there are no published data to describe the nature and the magnitude of in vivo metabolic drug-drug interaction between the 2 drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is used in WHO-recommended artemisinin combination therapy with artesunate (31). Mefloquine is mainly metabolized by CYP3A4, as was shown by coincubation/coadministration with the isozyme-specific inhibitor ketoconazole and the CYP3A4 inducer rifampin, both in human hepatocytes in vitro and human volunteers in vivo (24,32,33). The pharmacologically inactive carboxymefloquine (34) is regarded as the major metabolite (35).…”
Section: Discussionmentioning
confidence: 99%